Interacting Shell Model Calculations for Neutrinoless Double Beta Decay of 82Se With Left-Right Weak Boson Exchange - Iwata, Yoritaka; Sarkar, Shahariar (Frontiers in Astronomy and Space Sciences, 2021)
In the present work, the ++ mechanism (left-right weak boson exchange) and the light neutrino-exchange mechanism of neutrinoless double beta decay is studied. In particular, much attention is paid to the calculation of nuclear matrix elements for one of the neutrinoless double beta decaying isotope 82Se. The interacting shell model framework is used to calculate the nuclear matrix element. The widely used closure approximation is adopted. The higher-order effect of pseudoscalar term of nucleon current is also included in some of the nuclear matrix elements that result in larger Gamow-Teller matrix elements for the ++ mechanism. Bounds on Majorana neutrino mass and lepton number violating parameters are also derived using the calculated nuclear matrix elements.